Гендерное неравенство: теоретико-методологические подходы к интерпретации - Стрельник, Е. (Социология: теория, методы, маркетинг, 2005)
The article is aimed at the systematization of theoretical and methodological approaches to the analysis of gender inequality. The author has made a careful analysis of the main conceptions of gender inequality in modern sociological theory: functional and conflict points of view, feministic theories (liberal, Marxist, radical, and socialistic feminism) as well as stratification and constructivist approaches. Correlation between feministic and sociological positions in the research of gender relations is also a question of this paper.